Bilingualism effects on L1 representation and processing of argument structure. (1st August 2017) - de Oliveira, Cândido Samuel Fonseca; de Souza, Ricardo Augusto; de Oliveira, Fernando Luiz Pereira
This study aims to investigate L2-to-L1 cross-linguistic influence on bilinguals' representation and processing with three psycholinguistics tasks. The interest in this type of effect lies in its possible association with cognitive control development. Our study focuses on possible influences of the non-dominant language on the dominant language: we analyzed whether highly proficient Brazilian Portuguese-English late bilinguals immersed in the L1 context behaved differently from Brazilian Portuguese monolinguals in regards to sentences in the L1 that simulated an L2-specific construction (true resultative). We conducted a maze task in order to analyze the speakers' linguistic processing and a speeded acceptability judgment task in order to analyze their linguistic representation. We also observed participants' behavior towards a construction available in both languages (depictive). The overall results indicate that bilinguals processed both constructions faster than monolinguals, but the difference between the groups was significantly larger towards the true resultative construction. However, there was no significant difference between the groups in relation to how they perceived the acceptability of both constructions. We interpret the results as evidence that the L2 influence on the L1 occurs during real time sentence processing, but it does not result in changes in the overall L1 representation.